ANALYSIS OF EFFECT OF FIRM SIZE, INSTITUTIONAL OWNERSHIP, PROFITABILITY, AND LEVERAGE ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE AS INTERVENING VARIABLES (Study on Banking Companies Listed on BEI Period 2012-2016) - Astuti, Fitria Yuni; Wahyudi, Sugeng; Mawardi, Wisnu (JURNAL BISNIS STRATEGI, 2018)
The main objective of the company survives in the stringent competitive by maximizing the value of the company to shareholder wealth. Firm value is experiencing a downward trend is a problem that must be resolved. The banking company also undertakes a social responsibility that is perceived to have a positive impact on the company's image. This study aimed to analyze the effect of the firm size, institutional ownership, profitability, and leverage with corporate social responsibility (CSR) disclosure as a variable intervening.Populations are banking companies listed on the Indonesia Stock Exchange Period 2012-2016. Sampling technique used is purposive sampling with 29 companies selected according to predetermined criteria. This research is done by using multiple linear regression analysis methods and path analysis also Sobel test to examine the effect of intervening.Â Test results with CSRD as the dependent variable indicate that institutional ownership and Leverage have no effect on CSRD While firm size and profitability (ROA) have a positive significant effect on CSRD. The result of testing with Firm Value (Tobins'Q) as the dependent variable indicates that Firm Size, Institutional Ownership, and Profitability (ROA) have no effect on Firm Value (Tobins'Q). Leverage (DAR) has a negative and significant influence on FirmÂ  Value (Tobins'Q) while CSRD has a significant positive effect on Firm Value (Tobins'Q). CSRD does not mediate the effect of Institutional Ownership, Profitability (ROA) and Leverage (DAR) on Firm Value (Tobins'Q). CSRD mediates the effect of Firm Size on Firm Value (Tobins'Q).